Direct and Selective Synthesis of Adipic and Other Dicarboxylic Acids by Palladium‐Catalyzed Carbonylation of Allylic Alcohols. Issue 46 (15th September 2020) - Yang, Ji; Liu, Jiawang; Ge, Yao; Huang, Weiheng; Neumann, Helfried; Jackstell, Ralf; Beller, Matthias
Abstract: A general and direct synthesis of dicarboxylic acids including industrially important adipic acid by palladium‐catalyzed dicarbonylation of allylic alcohol is reported. Specifically, the combination of PdCl2 and a bisphosphine ligand (HeMaRaphos) promotes two different carbonylation reactions with high activity and excellent selectivity. Abstract : A general direct and selective synthesis of adipic acid and other dicarboxylic acids by palladium‐catalyzed dicarbonylation of allylic alcohol is reported. Specifically, the combination of PdCl2 and a bisphosphine ligand (HeMaRaphos) promotes two different carbonylation reactions as well as olefin isomerization with high activity.